Karakteristik Pasien TB Resisten Obat di Kalimantan Selatan : Studi Ekologi terhadap Kesiapan Implementasi Regimen BPaL/M - Sandi, Dita Ayulia Dwi; Nurrahma, Ika Maulida; Isnani , Nazhipah (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
This study aims to describe the prevalence and analyze risk factors associated with the incidence of Drug-Resistant Tuberculosis (DR-TB), as well as to analyze the readiness of the implementation of the BPaL/M regimen in South Kalimantan based on patient characteristics. This study used an observational-analytical approach with a cross-sectional design. Data were obtained from the South Kalimantan Provincial Tuberculosis Information System in 2022-2023. The study sample consisted of 151 patients with DR-TB. The chi-square test was used for statistical analysis. The incidence of DR-TB in South Kalimantan in 2023 was 0.95%, with the highest incidence coming from Banjarmasin City, namely 37.36%. Drug-resistant tuberculosis (DR-TB) in South Kalimantan was most common in the elderly (>45 years) (54.30%), men (62.91%), unemployed (56.29%), and non-pregnant (98.68%). Most drug-resistant TB patients were individuals who had undergone previous treatment (63.58%), did not have comorbid DM (75.50%) and were HIV negative (98.68%). A total of 76.16% received a short-term therapy regimen and 94.70% of RO-TB patients in 2022-2023 met the criteria for receiving BPaL/M regimen therapy. The conclusion of this study is that the factors that influence the incidence of RO-TB in South Kalimantan are occupation (p 0.016), history of previous TB treatment (p 0.000) and HIV status (p 0.000), the BPaL/M regimen with a shorter duration (6 months) can be implemented in RO-TB patients in South Kalimantan by continuously improving monitoring to achieve and reduce side effects of drug events.